A metabolic oscillator controls temporal changes in lipid metabolism and redox Istatus in tumor cells : implications in chemotherapy suceptibility - Wagner, Paula M.; Monjes, Natalia M.; Guido, Mario E. (2019)
Biological clocks even present in immortalized cell lines, regulate physiological processes in a time-dependent manner, driving transcriptional and metabolic rhythms. The disruption of circadian rhythmicity in modern life (shiftwork, jetlag, etc.) may promote higher cancer risk and metabolic disorders.